أثار وسائل الإعلام في عملية التنشئة الاجتماعية (مقاربة نظرية) - لغرس, سوهيلة (جامعة الوادي - University of Eloued, 2022)
الهدف من هذا البحث هو معرفة الآثار الإيجابية والسلبية التي تخلفها وسائل الإعلام في عملية التنشئة الاجتماعية داخل المجتمع، فالتنشئة الاجتماعية هي عملية مستمرة مدى الحياة يكتسب من خلالها الأفراد القيم والمعايير الاجتماعية التي تتعلق بثقافة مجتمع ما، وتعتبر وسائل الإعلام عنصرا هاما لعملية التنشئة، فهي مسؤولة عن تشكيل شخصية الأفراد، فالتعرض المتكرر لوسائل الإعلام يمكن الفرد من أن يتعلم المهارات المعرفية و الاجتماعية و الثقافية والآثار طويلة المدى لسلوك الأفراد وتنمية القيم ورؤية العالم. وفي الأخير ، لوسائل الإعلام أثارا قوية وكبيرة على مواقفنا وسلوكنا مما يجعلها عاملا هاماً في عملية التنشئة الاجتماعية. The aim of this research is to see the positive and negative effects the media plays in the socialization process in society, Socialization is a process across the life span through which individuals acquire and interact with values and social standards of a specific society and culture. Media are considered a powerful agent of socialization, responsible for shaping an individual’s, Findings suggest that repeated mass media exposure has potential for learning (cognitive, social, cultural skills) and long-term implications for behavior and the cultivation of worldview and values. Finally , Mass media has enormous effects on our attitudes and behavior which makes it an important contributor to the socialization process.
the Effects of Media in the Socialization Process )Theoretical Approach).
مقال
Keywords: التنشئة الاجتماعية ، وسائل الإعلام ، الأفراد، المجتمع، الثقافة.; socialization, mass media, individual’s , society, culture.